1978
DOI: 10.1111/j.1600-0722.1978.tb00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Rate of migration of oral leukocytes in patients with periodontitis

Abstract: The rate of migration of leukocytes (OMR) was estimated by counts of sequential mouthrinses in 81 human subjects in order to evaluate its usefulness as a laboratory test of oral inflammation. Periodontitis was taken as a model, and neither patients nor controls had any other oral inflammation. Patients with advanced periodontitis, but with periodontal destruction of about the same level, were divided into two groups, acute phase and chronic phase. The mean number of leukocytes entering the oral cavity in 30 s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…It has been previously shown that the rate at which oral neutrophils migrate into the oral cavity increases in the presence of inflammation (10) and that oral neutrophil counts positively correlate with both increasing pocket depth and the gingival index (11,12). Interestingly, Raeste & Aura (13) found that the leukocyte count in the first rinse of the OMR series also reflects the severity of periodontal disease. Although the definition of disease used in their study is unclear and inconsistent with the criteria described above, meaningful comparisons can still be made.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been previously shown that the rate at which oral neutrophils migrate into the oral cavity increases in the presence of inflammation (10) and that oral neutrophil counts positively correlate with both increasing pocket depth and the gingival index (11,12). Interestingly, Raeste & Aura (13) found that the leukocyte count in the first rinse of the OMR series also reflects the severity of periodontal disease. Although the definition of disease used in their study is unclear and inconsistent with the criteria described above, meaningful comparisons can still be made.…”
Section: Discussionmentioning
confidence: 99%
“…Although the definition of disease used in their study is unclear and inconsistent with the criteria described above, meaningful comparisons can still be made. Raeste & Aura's first rinse values exhibited a threefold higher leukocyte count in patients with chronic periodontitis than in healthy controls (13). A 25‐fold higher leukocyte count was noted in patients with acute periodontitis than in controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[32] Klinkhammer[33] standardized collection and counting of leukocytes in saliva and developed the orogranulocytic migratory rate (OMR). Raeste et al .,[34] in their study, indicated that the OMR reflects the presence of oral inflammation, and suggested that this measure can be used as a laboratory test.…”
Section: Salivary Markers Of Periodontal Diseasesmentioning
confidence: 99%